Reconstructing Indonesia’s 2029 Presidential Election System: Following the Abolition of the Presidential Threshold - Ilham Muhammad Yasir, (Proceeding International Conference on Social Sciences, 2026)
This paper analyzes the constitutional implications of Constitutional Court Decision No. 62/PUU-XXII/2024, which abolished the presidential threshold. This decision represents a critical shift in Indonesia’s electoral system, expanding opportunities for smaller parties and independent candidates to participate in the presidential election. While the abolition increases political inclusivity, it also raises significant concerns about political fragmentation and government legitimacy. The removal of the presidential threshold opens the door for more candidates to run, potentially leading to a fragmented political landscape and a president with minority support. This fragmentation could weaken the legitimacy of the elected government, particularly if no candidate achieves majority backing. To address these challenges, this paper proposes alternative electoral mechanisms such as the two-round system (runoff election), rankedchoice voting (RCV), and cross-regional support requirements for presidential candidates. These mechanisms aim to ensure majority support while maintaining political inclusivity and preventing fragmentation. In conclusion, while the abolition of the threshold enhances democratic participation, a careful redesign of the electoral system is necessary to balance inclusivity with the effectiveness and stability of Indonesia’s presidential system. This reworking is essential to maintaining a stable and legitimate government while expanding opportunities for diverse political voices in the 2029 presidential election.